Ethics in action - Corey, Marianne Schneider; Haynes, Robert ([S.l.] : Brooks/Cole, 2003)
On this interactive cd-rom, Jerry and Marianne Corey demonstrate an integrative approach to common ethical dilemmas in a variety of settings
Demonstrator: Gerald Corey, Marianne Schneider Corey, Robert Haynes
System requirements: Microsoft Windows: Pentium or compatible class chip, Windows 95/98/NT 4.0 or higher, 32 MB RAM, CD-ROM drive (10x or faster), SVGA monitor capable of supporting 800x6000 resolution at 16 bit, sound card (note: for Windows 2000, a Pentium 1.33 or higher chip and 64 MB of RAM are required ; Macintosh: PowerPC, OS 7.6.1 or higher, 32 MB of free RAM, CD-ROM drive 910x or faster) SVGA monitor capable of supporting 800x600 resolution at 16 bit.
Keywords: Ethics